157 An Alternative Option for Gender-Affirming Revision Vaginoplasty: The Tubularized Urachus-Peritoneal Hinge Flap. Issue 1 (1st April 2022) - Yuan, N.; Gupta, A.; Garcia, M.
ABSTRACT: Introduction: Peritoneal vaginoplasty (PV) has been reported for congenital and primary gender-affirming cases, but few have reported its use as secondary vaginoplasty to treat post-op neovaginal canal shortening after penile-inversion vaginoplasty (PIV). Recent adaptations of PV have been modifications of the Davydov procedure, wherein peritoneum adherent to the bladder and rectum are incorporated to line the new terminal apex of the vaginal canal. Objective: We describe our alternative technique using a urachus-peritoneal hinge flap and discuss proposed advantages. Methods: We performed retrospective review of all trans-female patients who underwent our PV technique for revision/salvage vaginoplasty from May 2019 to August 2020 (minimum 10 months follow-up). Patients were asked questions about their experience and satisfaction. All cases were performed via combined trans-perineal and laparoscopic (robot-assisted) approaches. Pre-op and post-op neovaginal depth/circumference were recorded. After incision and spatulation of the terminal neovagina, a midline, inferiorly based peritoneal hinge flap (minimum 8-cm width) was elevated craniocaudally from the umbilicus to the mid-posterior bladder. The flap's free end was flipped posteriorly and sutured to the posterior edge of the open canal remnant to form a peritoneum-lined pouch. The pouch's lateral edges were sutured together, using a vaginal dilator as a guide. Results: Five patients underwent peritoneal vaginoplasty with our technique from 5/2019 to 8/2020. Mean age was 32. All previously underwent PIV for primary vaginoplasty, with loss of neovaginal depth. Pre-op: mean neovaginal depth was 8.6 (±1.8) cm and girth was 12 cm. Immediate post-op: mean depth was 16.8 (±1.2) cm (mean net increase from pre-op: 8.2 cm) and girth was 12 cm. At mean follow-up of 1.4 years, mean depth was 12.8 (±2.4) cm (mean net increase from pre-op: 4.2 cm) and girth was 12 cm. There were no immediate complications. One patient developed anastomotic stenosis at 6 weeks post-op, managed conservatively with dilation under anesthesia. One patient stopped dilating due to a mental-health crisis and lost significant postoperative depth. Three of the 5 (60%) patients report satisfactory vaginal receptive intercourse. The other 2 have not yet attempted vaginal receptive intercourse. Conclusions: Our PV vaginoplasty technique is a safe and effective option to treat neovaginal shortening after PIV. Advantages include no tension on peritoneal suture lines when vaginal canal is empty and total exclusion of the rectum. This technique also allows for omental interposition. We recognize the natural limited availability of peritoneum and so reserve this technique only for cases where there is adequate residual canal girth and at least 6-7 cm of residual depth. Disclosure: No